Russia - Wallace, Donald Mackenzie, 1841-1919 (Salt Lake City, UT : Project Gutenberg, 2006)
"Russia" by Donald Mackenzie Wallace is an extensive travelogue and observational account written during the late 19th century. The book explores various aspects of Russian life, geography, and culture, reflecting on the author's experiences and observations during six years of residence in the country, complemented by additional visits and studies over a span of decades. It provides insights into the complexities of travel, the interactions with diverse populations, and the socio-political dynamics within Russia, addressing themes of modernization and tradition juxtaposed against a backdrop of cultural richness. The opening of "Russia" introduces readers to the author's impressions of traveling in the country, highlighting the challenges and quirks of the railway and road systems. Wallace describes the comforts and discomforts of railway travel, the peculiar customs of Russian hotels, and the lively characters he encounters, including peasants and traders. His narrative captures the occasionally chaotic and humorous aspects of navigating logistics in a vast land, shedding light on the realities of Russian transportation infrastructure at the time. He reflects on the cultural contrasts between urban and rural life, setting the stage for further explorations of peasant society, local customs, and his quest to learn the Russian language throughout his journey. (This is an automatically generated summary.)
Release date is 2006-05-03
Donald Lainson and David Widger
Keywords: Russia -- Politics and government -- 1801-1917; Russia -- Religious life and customs; Nobility -- Russia; Peasants -- Russia; Industries -- Russia -- History -- 19th century